Peculiarities of Ensuring Legality in the Public Administration System - B. V. Rossinskiy (Courier of Kutafin Moscow State Law University (MSAL)), 2026)
It has been determined that public administration and the public administration system, not being mentioned in any legislative acts, and being currently only purely scientific categories, are understood differently in the literature. It is noted that, in addition to state and municipal bodies, organizations implementing publicly significant functions and vested with specific state powers have inevitably come to be considered public administration entities. It is concluded that the specific nature of the very concept of “public administration” inevitably implies the significant participation of civil society institutions in its implementation, and that, overall, the public administration system consists of three subsystems. It is argued that the integrated degree of prevention, detection, and suppression of violations of the law within the public administration system as a whole, when properly organized, is higher than the respective combined capabilities of all three subsystems comprising this system individually.